Quaternary ammonium salt–modified polyacrylonitrile/polycaprolactone electrospun nanofibers with enhanced antibacterial properties. Issue 19 (October 2021) - Zhang, Hongnan; Zhang, Tingting; Qiu, Qiaohua; Qin, Xiaohong
In this experiment, octadecyltrimethylammonium chloride (STAC), a cationic antibacterial agent, was designed to modify hydrolyzed polyacrylonitrile (PAN) through tight electrostatic attraction. Then, the modified PAN was successfully electrospun with polycaprolactone (PCL) to obtain PCL/PAN-STAC nanofibrous membranes with enhanced mechanical properties. The modified PAN was characterized by Fourier transform infrared spectroscopy, thermogravimetric analysis and elemental analysis. The morphological, mechanical and antibacterial properties of nanofibrous membranes were investigated. The blended nanofibrous membrane presented a uniform and stable structure with small pore size. Tensile tests indicated that the mechanical property of PCL/PAN-STAC nanofibrous membrane was obviously enhanced by blending. Disk diffusion tests showed that the inhibition zones of PCL/PAN-STAC against Escherichia coli and Staphylococcus aureus were 7.56 ± 0.05 mm and 15.37 ± 0.34mm, , respectively. Shaking method indicated that the antibacterial activity against E. coli was as high as 96.20 ± 0.89% when the use of PCL/PAN-STAC reached 9 mg. Therefore, this antibacterial nanofibrous membrane is very favorable for applications such as protective filtration masks and wound dressing.